Effect of Vacuum Freeze-drying Process Parameters on Acid Paper Literatures - Zhan Yanping; Li Chao; Yu Yuejin; Hu Wan; Zhang Jinping; Zheng Dongqing (Zhileng xuebao)
Acid paper documents are selected as the research subject, and the influence of procedure parameters (heating temperature, paper document thickness, pressure in drying room) on freeze-drying time and quality were explored, and obtained the sequence of importance and dehydration rate by orthogonal method. The results indicate that the different treatment levels of procedure parameters had remarkable influence on both vacuum freeze-drying time and the quality, and the importance sequence of the three factors both as follows: paper documents thickness, heating temperature, and pressure in drying chamber. The optimal parameters were a thickness of 7mm, heating temperature of 25℃ and pressure of 10~20Pa by optimization analysis.